ORGANIC AND ANORGANIC TECHNIQUE OF FERTILIZATION TO INCREASE OF PALU’S SHALLOT PRODUCTIVITY - Ruslan Boy (Pusbindiklat - LIPI, 2011)
Palu’s shallot is commercial crops. The productivity of Palu’s shallot is still a lower compared to that in regional crop which was achieved of 6,1 t/ha. In addition, this production is still lower compared to the national productivity (20 t/ha). This research was aimed to study the application of organic and inorganic fertilizers in the productivity of Palu’s shallot. The study was arranged in a randomized block design with 5 treatments and 4 replications. This study was performed on farm of fearmer’s land at Guntarano village of Tanatovea sub-district of Donggala district. The treatment consisted of ZA 100 kg/ha + NPK (P0), compost of cow excrement 10 t/ha (P1), compost of chickeent excrement 5 t/ha (P2), compost of goat manure 5 t/ha (P3), compost of cow excrement 5 t/ha + ZA 50 kg/ha. Result indicated that all treatments showed not signifi cant on vegetative growth of local Palu’s shallot. However, there was a signifi cant effect among the fertilizer treatments on increasing of Palu’s shallot productivity. It was found that the weight of wet tuber showed higher than in P4 (14.42 t/ha) and in P2 (10.90 t/ha).